PENGARUH LITERASI KEUANGAN SYARI'AH, AKSESBILITAS, PERILAKU KEUANGAN DAN MOTIVASI TERHADAP MINAT MASYARAKAT PADA PENGGUNAAN JASA PERBANKAN SYARI'AH - Septiawan, Agung; Safei, Abdulah; Fitri, Yuda Septia (Likuid Jurnal Ekonomi Industri Halal, 2022)
The population growth of the City of Tasikmalaya is a potential target market for Islamic banking, the population of the City of Tasikmalaya should be able to increase the market share of Islamic banking in West Java which is at 8.36% and increase the use of Islamic banking. This study aims to determine how much influence Islamic financial literacy, accessibility, financial behavior and motivation have on the interest of the people of Tasikmalaya City in the use of Islamic banking services. The method used in this study is a quantitative method with hypothesis testing on data analysis techniques, namely multiple linear regression test. The findings in this study are that the variables of Islamic financial literacy and motivation show an influence on the interest of the people in use of Islamic banking services. Then on the accessibility and financial behavior variables, it shows that there is no influence on the interest of the people in use of Islamic banking services. Based on the conclusions in this study, it shows that the influence of Islamic financial literacy, accessibility, financial behavior and motivation on the interest of the people in use of Islamic banking services is 57.4%.